Effects of a single, 24-hour, low-dose intravenous dobutamine infusion on left ventricular myocardial performance index in congestive heart failure: A prospective, nonrandomized study - Ulucam, Melek (Elsevier, 2005)
BACKGROUND: Dobutamine, a predominantly beta-adrenergic sympathomimeticagent, is used for improving left ventricular (LV) systolic performance with different dosing regimens in patients with congestive heart failure (CHF). Myocardial performance index (MPI) is an indicator of LV global function that is correlated with LV end-diastolic pressure, and it is increased in CHF. OBJECTIVE: The purpose of this study was to examine the effects of a single, 24-hour, low-dose, IV dobutamine infusion on LV systolic and diastolic function and on MPI in CHF as an indicator of LV global function, as well as the adverse effects (AEs) of the infusion. METHODS: This prospective, nonrandomized study was conducted at theDepartment of Cardiology, Baskent University Hospital, Ankara, Turkey. Adult patients with LV ejection fraction (EF) <35%, sinus rhythm, and symptomatic CHF were treated using a standard protocol for at least 4 weeks. At the end of this period, patients with symptomatic CHF and EF <35% underwent echocardiography that included measuring isovolumic relaxation and contraction times (IRT and ICT, respectively) and LV ejection time (ET), and calculating LV MPI using the formula MPI = (IRT + ICT)/ET Dobutamine 2.5 μg/kg · min was then infused intravenously for 24 hours. Echocardiography was repeated 24 hours later and values were compared with preinfusion data. Patients were observed and monitored for CHF symptoms and AEs for 24 hours. RESULTS: Forty-three patients were enrolled in the study, and 31 (22 men,9 women; mean [SD] age, 67.55 [11.78] years) continued after the 4-week standard-treatment period. Mean (SD) heart rate (74.93 [20.15] vs 80.23 [13.74] bpm, respectively), systolic blood pressure (129.00 [19.23] vs 126.67 [23.79] mm Hg), and diastolic blood pressure (75.80 [11.26] vs 74.96 [8.30] mm Hg) were statistically similar before and after the infusion. The mean (SD) end-diastolic volume was statistically similar to the preinfusion value (215.87 [76.74] vs 211.08 [65.51] mL); however, the mean (SD) end-systolic volume was significantly reduced (163.80 [63.86] vs 146.74 [53.12] mL; P = 0.01). Mean (SD) EF (25.33% [7.77%] vs 30.45% [7.63%]; P = 0.001) and stroke volume (SV) (54.92 [22.30] vs 63.59 [23.91] mL; P = 0.04) increased significantly. The mean (SD) early:late diastolic flow velocity (E/A ratio) (1.58 [1.36] vs 1.65 [1.27]), IRT (107.03 [35.37] vs 100.42 [34.32] ms), ICT (96.61 [34.27] vs 86.35 [44.80] ms), ET (240.65 [33.28] vs 243.48 [33.54] ms), and MPI (0.81% [0.28%] vs 0.78% [0.31%]) did not change significantly after dobutamine infusion. No AEs were observed. CONCLUSIONS: In this study of adult patients with symptomatic CHF, a single, 24-hour, low-dose, IV dobutamine infusion (2.5 μg/kg · min) was associated with decreased LV end-systolic volume and increased SV and EF However, LV diastolic function parameters, isovolumic time intervals, ET, and MPI were statistically similar to preinfusion values. The infusion was well tolerated.